Three phase oil-immersed distribution transformers, 50 Hz, from 50 to 2500 kVA with highest voltage for equipment not exceeding 36 kV. Distribution transformers with cable boxes on the high voltage and/or low voltage side. General requirements Part 2.1, (15th September 1995) - British Standards Institution,
No abstract available